Dampak Cultural Invasion terhadap Kebudayaan Lokal: Studi Kasus Terhadap Bahasa Daerah - Gema Budiarto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2020)
Culture is an essential aspect of the human civilization that can show life activities. The life of human cannot escape from a culture, therefore can be said the human is the core of culture. Human existence is a sign of culture existence cause human is the creator of culture. The cultural development in every single region or country will be different and have typical characteristics with each other. The formulation of the problem in this research is how the impact of cultural invasion on local culture, especially indigenous language. This article aims to discuss the impact of the cultural invasion on local culture (mother tongue), the cultural invasion is a threat to the mother tongue if the testator of the local culture cannot maintain his cultural identity. The research method is the qualitative method with the literature study and observation approach. The results showed that cultural invasion has a significant impact on mother tongue. Cultural invasion utilizing global communication as an effort to offering his ideas. The spreader of the ideas has the claim that his culture is better than another. So, it can affect and suppress the local culture in general and mother tongue in particular.